2011
DOI: 10.1111/j.1751-553x.2011.01354.x
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of liquid-stored and lyophilized reconstituted human infusible platelet membranes

Abstract: This study revealed the potential of IPM microvesicles to mimic the binding features of platelets in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Whereas we found that the maximum binding of IPM to vWF occurred with the IPM prepared in the 0.25 or 0.4 M concentration of sodium octanoate. So, the ability of IPM to bind to vWF was dependent on the concentration of the stabilizer [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas we found that the maximum binding of IPM to vWF occurred with the IPM prepared in the 0.25 or 0.4 M concentration of sodium octanoate. So, the ability of IPM to bind to vWF was dependent on the concentration of the stabilizer [18].…”
Section: Discussionmentioning
confidence: 99%
“…Platelets were used to produce IPM as it was reported before [18]; briefly; these cells were lysed by replicate freezing and thawing for 3 times, virally inactivated by moist heat at 60°C for 20 h with different concentrations of sodium octanoate (0, 0.1, 0.25, 0.4, 0.6 M). IPM were divided into vials and kept in refrigerator.…”
Section: Preparation Of Ipm and Isolation Of Npmpsmentioning
confidence: 99%
“…The expression of gpIIb/IIIa in this study could not be attributed to the platelets remained in the IPM preparation because the size of prepared IPM microparticles was determined to be in the range of 84.7-291 nm (Z-average = 174 nm) [15] that had no correlation with the size of platelets.…”
Section: Discussionmentioning
confidence: 72%
“…Alternatively, the main cause of the difference may be related to the preparation method as its effect was elucidated in our study using different concentrations of the heat stabilizer but the use of heat protection method were not explained in the work of Chao. Our previous study showed that during the heating step of IPM preparation the usage of a heat stabilizer (sodium octanoate) was necessary to obtain the maximum vWF binding activity of IPM [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation